Assessing Actual Visit Behavior through Antecedents of Tourists Satisfaction among International Tourists in Jordan: A Structural Equation Modeling (SEM) Approach - Muala, Ayed Moh’d Al; Mat, Nik Kamariah Nik; Isa, Filzah Mohd (ASEAN Marketing Journal, 2021)
Jordan tourism industry is facing fluctuating tourist visit provoked by dissatisfaction, high visit risk, low hotel service, or negative Jordan image. This study aims to examine the relationships between the antecedents of tourist satisfaction and actual visit behavior in tourism of Jordan, and the mediating effect of tourist satisfaction (SAT) in the relationship between Jordan image (JOM), service climate (SER) and actual visit behavior (ACT). A total of 850 international tourists completed a survey that were conducted at southern sites in Jordan. Using structural equation modeling (SEM) technique, confirmatory Factor Analysis (CFA) was performed to examine the reliability and validity of the measurement, and the structural equation modeling techniques (Amos 6.0) were used to evaluate the casual model. Results of the study demonstrate the strong predictive power and explain of international tourists’ behavior in Jordan. The findings highlighted that the relationship between Jordan image and service climate are significant and positive on actual visit behavior.